Outcomes of frontal mucoceles treated with conventional endoscopic sinus surgery. (August 2015) - Nomura, Kazuhiro; Hidaka, Hiroshi; Arakawa, Kazuya; Sugawara, Mitsuru; Ozawa, Daiki; Okumura, Yuri; Takata, Yusuke; Katori, Yukio
Abstract Conclusion: Conventional endoscopic sinus surgery (CESS) is useful for frontal mucoceles. A patient with short anterior–posterior distance and bone thickening may need an axillary flap, Draf type IIb, or Draf type III procedure. Objective: To present outcomes of frontal mucoceles treated with CESS and predict risk factors for poor outcomes to help define surgical indications. Methods: A consecutive clinical series was reviewed retrospectively. The authors performed CESS without agger nasi resection (Draf type IIa) for 13 frontal sinus mucoceles in 12 patients between October 2011 and July 2013. Patient age, sex, blood eosinophil count, history of operation and co-existence of acute infection were compared. For the condition of the frontal sinus, anterior–posterior distance and width of frontal recess, bone thickening of the frontal recess, bone absorption due to continuous pressure by mucocele and anatomy of the frontal recess was noted. Results: All operations were done without a navigation system. The post-operative course was uneventful in all 12 patients, and all symptoms gradually receded. Among 13 mucoceles, one frontal sinus (7.7%) closed during follow-up.